The Effect of Organic Liquid Fertilizer Application on Fish Pond’s Water Quality at the Reclaimed Indonesian Tidal Lowland - Fitrani, Mirna; Marsi, Marsi; Susanto, Robiyanto H; Dewi, Santa (Indonesian Aquaculture Society (MAI), 2016)
Organic liquid fertilizer is the source of nutrients. This fertilizer can be used to improve the water quality. It is enviromentally friendly and relatively cheap. Application of the fertilizer has been done on aquaculture. At the tidal lowland areas, application of this fertilizer is mostly as soil improvement agent. It is limited to be used as water quality improvement agent. Tidal lowland has an acid soil with a low fertility level characters. The objectives of the study are to know the effect of liquid organic fertilizer to the water quality (temperature, pH, dissolved oxigen, ammonia) and to the amount of plankton in the ponds. This research was done at the reclaimed tidal lowland in Banyuasin District of South Sumatera, Indonesia. The organic liquid fertilizer was made by fermentation of both animals manures and vegetable waste with the percentage of N : P2O5 : K2O were 0.120 : 0.023 : 0.750. Water quality data was taken three times in every three days (plankton) from the ponds that was added by liquid fertilizer with dose of 4.35 L /pond (P1) and 8.7 L/pond (P2). All the water quality data were analyzed qualitatively. The results show that on treated ponds pH dropped slightly since the beginning with pH 6.0 and remain 6.4 - 6.8 in the last day. The value of Ammonia ranges 0.06-0.15 mg.L-1 and Dissolve oxigen range 1.9-2.5 mg.L-1‑. Phytoplankton and zooplankton amount increased and reached the peak on day 12 (12033 ind.L-1 and 364 ind.L-1 respectively), and finally turned down slowly. Therefore, liquid fertilizer addition should be given to the ponds more than once during fish rearing period. It is in order to increase the amount of plankton and to manage the water quality in the reclaimed tidal lowlands ponds